Implementasi Teknologi pada Aspek Pakan dan Pemasaran di Kelompok Usaha Ransum Pakan Ternak di Kabupaten Padang Pariaman - Ediset Ediset; Adrizal Adrizal; Firda Arlina; Eli Ratni (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
The community engagement team of the Animal Science Faculty of Andalas University conducted community services in the Animal Feed Ration Business group in Jorong Batang Sarik, Nagari Katapiang, Batang Anai District, Padang Pariaman Regency. The problems in the target group were 1) the business group still needs to get a permit to do business, and 2) it still needs to gain skills in processing feed for cattle based on agricultural waste. The activity aimed to assist business groups in obtaining Business Permit Numbers (BPN) and transferring agricultural waste-based feed technology for beef cattle. The transfer of knowledge and technology in service activities was carried out by mentoring, demonstration, and training methods regularly and continuously. The action resulted that the target group having a business permit in the form of BPN and the business group having knowledge and skills in producing feed for beef cattle in the form of Complete Ration Silage (CRS) based on corn straw.